Applications of Terahertz Spectroscopy in the Detection and Recognition of Substances - Fu, Xiaojian; Liu, Yujie; Chen, Qi; Fu, Yuan; Cui, Tie Jun (Frontiers in Physics, 2022)
Recently, terahertz spectroscopy has received a lot of attention because of its unique properties such as biosafety, fingerprint spectrum, and good penetration. In this review, we focus on the research progress of terahertz spectroscopic techniques for the detection and recognition of substances. First, we describe the fundamentals of terahertz spectroscopy. Then, we outline the applications of terahertz spectroscopy in biomedicine, agriculture, food production, and security inspection. Subsequently, metamaterials, which have recently received extensive attention, are also investigated for the applications in terahertz spectroscopic detection and recognition of substances is illustrated. Finally, the development trend of terahertz spectroscopy for substance detection and recognition is also prospected.